Role of FKBP5 and its genetic mutations in stress-induced psychiatric disorders: an opportunity for drug discovery - Malekpour, Mahdi; Shekouh, Dorsa; Safavinia, Mohammad Ebrahim; Shiralipour, Shadi; Jalouli, Maryam; Mortezanejad, Sahar; Azarpira, Negar; Ebrahimi, Niloofar Dehdari (Frontiers in Psychiatry, 2023)
Stress-induced mental health disorders are affecting many people around the world. However, effective drug therapy for curing psychiatric diseases does not occur sufficiently. Many neurotransmitters, hormones, and mechanisms are essential in regulating the body's stress response. One of the most critical components of the stress response system is the hypothalamus-pituitary-adrenal (HPA) axis. The FKBP prolyl isomerase 51 (FKBP51) protein is one of the main negative regulators of the HPA axis. FKBP51 negatively regulates the cortisol effects (the end product of the HPA axis) by inhibiting the interaction between glucocorticoid receptors (GRs) and cortisol, causing reduced transcription of downstream cortisol molecules. By regulating cortisol effects, the FKBP51 protein can indirectly regulate the sensitivity of the HPA axis to stressors. Previous studies have indicated the influence of FKBP5 gene mutations and epigenetic changes in different psychiatric diseases and drug responses and recommended the FKBP51 protein as a drug target and a biomarker for psychological disorders. In this review, we attempted to discuss the effects of the FKBP5 gene, its mutations on different psychiatric diseases, and drugs affecting the FKBP5 gene.